Application of Data Encryption Technology in Computer Network Information Security - Li, Lifeng (Security and communication networks, 2022)
In order to solve the partial optimization problems of the RSA algorithm in computer network security, a method of RSA algorithm optimization based on data encryption was proposed. In the research, the application of data encryption in network information security system was mainly investigated, using RSA as the representative algorithm in the public key cryptosystem. The network information security model on the basis of data encryption was built on the public key cryptosystem in the research. Through the introduction of the RSA algorithm and the corresponding optimization scheme, the experiments for comparison were set up. Through the experiments, the feasibility of the optimization scheme was verified. Experimental results show that the efficiency of the RSA algorithm was about 1.0% to 2% higher than that of the traditional algorithm after a reasonable selection of parameters and the use of an optimized algorithm (also known as the combination algorithm), which improved the efficiency of RSA algorithm to a certain extent and achieved the purpose of improving RSA algorithm. It was proved that the method could effectively improve the budget efficiency of the RSA algorithm and solve the optimization problem of the RSA algorithm in computer network security.